Elite coaches' role in athletes' retirement transitions: a foucauldian discourse analysis - Brown, C. J. (International Sport Coaching Journal, 2025)
The aim of the research was to understand how prominent sociocultural discourses influenced how coaches construct athletes` transition out of sport and position themselves within the process of retirement. Interviews with eight male elite coaches were analysed using a Foucauldian Discourse Analysis. Coaches` talk about athletes` transitions out of sport was constructed within the dominant performance discourse in sport. This suggests years of adhering to disciplinary practices of elite sport left athletes underprepared for the next steps in their life. Even when constructing retirement in more positive terms, this was done in ways that drew on ideas of high performance and objective success. Coaches` own positions within transitions were discussed by drawing on ideas from a patriarchal construction of the coach-athlete relationship. Here, coaches are positioned as father figures with responsibility for guiding athletes through their careers and transitions out of sport. However, coaches suggested that the policies, procedures, and processes within wider networks of power inside sport often restricted their capacity to support athletes during their transitions. Future research and practice are aimed at helping coaches to navigate the power dynamics of sporting structures and organisations.